The Physical Concepts on Special Tube Surfaces Generated by Normal Curves in Galilean 3-Space - Almaz, Fatma; Kulahci, Mihriban Alyamac (My University, 2023)
In this study, we examine the tube surfaces formed by normal curves in Galilean 3-space, and we give Clairaut’s theorem on the tube surfaces using geodesic normal curves. Also, we attempted to explain why the specific kinetic energy and angular momentum of particles may be on tube surfaces.
Keywords: Galilean space; tube surfaces; Clairaut’s theorem; normal curves; the specific kinetic energy; the specific angular momentum